Seasonal hydrological traits in Salix psammophila and its responses to soil moisture and meteorological factors in desert areas. (March 2022) - Chen, Yunfei; He, Junqi; He, Yi; Gao, Wande; Zheng, Ce; Liu, Xiuhua
Highlights: Salix. psammophila sap flow exhibited considerable seasonal hydrological process. Different factors drive the seasonal hydrological process. Using deep soil storage water or temporarily stopping transpiration to tolerates winter water stress. Appropriate S. psammiphlia planting density is 10–20 m 2 in the Mu Us Desert. Abstract: Drought is a key factor limiting vegetation water use and growth. More frequent and extreme drought events are increasing around the world, which may affect plant physiological reactions and vegetation restoration activities. The present study explored the seasonal trends of sap flow in Salix psammiphlia (Sf ) by continuously collecting data on abiotic factors (net radiation [Rn ], atmospheric relative humidity [Rh ], atmospheric temperature [T], saturated vapor pressure difference [VPD], wind speed at 2 m height [U2 ], soil water storage [SWS], soil temperature [ST]) and transpiration rate (Ts ) in the Mu Us Desert. According to the results, Sf exhibited considerable seasonal trends accompanied by a unimodal pattern during the growing season, and with a bimodal pattern during the dormant season. Notably, the ratio of nocturnal sap flow to whole daily sap flow could increase by up to 100% (from October to December and March to May). Multivariate stepwise regression and structural equation modeling results suggested that different factors drive the seasonal trends. During the growing season, Rn, VPD, and U2 controlled Ts directly (R 2  = 0.80). While Ts was directly controlled by Rh, T, U2, SWS2 (20–100 cm) and ST_50 during the dormant season (R 2  = 0.43). Topsoil freezing in winter may led to water stress in S. psammiphlia, and then appeared the bimodal pattern. The plants survived freezing drought water stress by using the soil moisture stored in the deep soil layer (50–100 cm) and reducing Ts, or even temporarily stopping transpiration. According to this data, the threshold of S. psammophila in the region was estimated to be 480–540 clusters/ha 2 . These findings could guide ecosystem restoration activities and facilitate sustainable development in dry and degraded regions.